Does Gray Squirrel (Sciurus carolinensis) Response to Heterospecific Alarm Calls Depend on Familiarity or Acoustic Similarity?. (26th August 2013) - Getschow, Cynthia M.; Rivers, Pearl; Sterman, Samantha; Lumpkin, David C.; Tarvin, Keith A.
Abstract: In habitats in which multiple species are prey to the same predators, individuals can greatly benefit from recognizing information regarding predators that is provided by other species. Past studies have demonstrated that various mammals respond to familiar heterospecific alarm calls, but whether acoustic similarity to a familiar call can prompt a mammal's recognition of an unfamiliar call has yet to be shown. We presented alarm calls to free‐ranging eastern gray squirrels ( Sciurus carolinensis ) and recorded behavioral changes in vigilance and antipredatory response. Playbacks included alarm calls of a sympatric bird (American robin, Turdus migratorius ), an allopatric bird with a call structure similar to that of the robin (common blackbird, Turdus merula ), and an allopatric bird with a distinct call structure (New Holland honeyeater, Phylidonyris novaehollandiae ). Squirrels responded significantly more frequently to squirrel alarm calls (positive control) than to robin song (negative control) or honeyeater calls. Squirrel response to robin and blackbird alarm calls was statistically similar to their response to squirrel alarm calls, indicating that squirrels responded to those alarm calls as if they provided information about the presence of predators. However, squirrel response to robin song was not statistically different from response to any of the other avian calls, including the robin and blackbird alarms, suggesting that squirrels neither respond to blackbird alarms as if they clearly signify danger, nor as if they clearly do not signify danger, perhaps reflecting some ambiguity in interpretation of the calls. These results suggest that squirrel responses to alarm calls are generally based on call familiarity, but that acoustic similarity of an unfamiliar allopatric call to a familiar call also can elicit antipredator behavior. The lack of response to honeyeater alarm calls also supports the hypothesis that call recognition by gray squirrels is dependent on familiarity, rather than simply detection of an acoustic feature common to alarm calls across a variety of avian species.